Clinical effectiveness of Osigraft in long-bones non-unions. (December 2015) - Calori, Giorgio Maria; Colombo, Massimiliano; Bucci, Miguel; Mazza, Emilio Luigi; Fadigati, Piero; Mazzola, Simone
Abstract: Current evidence, based primarily on case series, suggest that the eptotermin alfa (recombinant bone morphogenetic protein-7 (rhBM-7)), which is commercialized as Osigraft with an indication for tibial non-union, used in monotherapy or polytherapy, is a safe and effective therapy for long bones non-unions of lower and upper limbs. No previous study has compared the safety and the efficacy of Osigraft and the "gold standard" treatment for recalcitrant long-bones non-union, autologous bone graft (ABG). This study aims to compare the effectiveness of Osigraft and ABG in the treatment of post-traumatic, persistent long bone non-unions. In particular, the present study will focus exclusively on complex persistent non-unions, excluding simpler cases, in which it is likely that a simple revision of the osteosynthesis will be sufficient to promote union, and extremely severe cases in which there is an indication for amputation and prosthesis. The study addresses the following research question: 1. Is the effectiveness of eptotermin alfa comparable to that of ABG in the treatment of complex long bone non-unions? 2. Are there significant differences in the prevalence of adverse events between patients treated with eptotermin alfa and those treated with ABG? The study is an observational, retrospective study, located in one Experimental Recruiting Center (Ospedale Universitario G. PINI – Milano). The study was conducted with ethics approval and according with the existing Italian law. Demographic and clinical data were collected from patients Clinical Medical Records and other existing documentation, through a web based eCRF. The treatment (surgery with Osigraft or ABG) effectiveness was evaluated comparing the number of success cases (primary endpoint) and the length for clinical and radiological healing (secondary end-points). The treatment safety was evaluating comparing the prevalence of Adverse Events. Osigraft was demonstrated to be statistically equivalent to ABG with respect to the primary and secondary end point of surgical success. The treatment success was statistically comparable across all the anatomical regions considered, both in patients treated with Osigraft and in patients treated with ABG. The use of Osigraft when compared to autograft was associated with statistically lower intraoperative blood loss and shorter operative times. In addition patients treated with Osigraft developed statistically less peri-operative and late onset adverse events, compared to ABG. The difference was substantially due to the occurrence of pain at donor site in patients treated with ABG.